2014
DOI: 10.4062/biomolther.2014.020
|View full text |Cite
|
Sign up to set email alerts
|

Luteolin Inhibits the Activity, Secretion and Gene Expression of MMP-3 in Cultured Articular Chondrocytes and Production of MMP-3 in the Rat Knee

Abstract: We investigated whether luteolin affects the gene expression, secretion and activity of matrix metalloproteinase-3 (MMP-3) in primary cultured rabbit articular chondrocytes, as well as production of MMP-3 in the rat knee to evaluate the potential chondro-protective effects of luteolin. Rabbit articular chondrocytes were cultured in a monolayer and IL-1β-induced gene expression levels of MMP-3, MMP-1, MMP-13, a disintegrin and metalloproteinase with thrombospondin motifs-4 (ADAMTS-4), ADAMTS-5 and type II colla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 37 publications
2
21
0
1
Order By: Relevance
“…Previous studies have shown increased expression of MMPs, COX-2, and iNOS following stimulation of chondrocytes by IL-1β [25]. Thus, the results indicate that nobiletin exerts antiinflammatory effects via attenuation of NF-κB activity.…”
Section: Discussionsupporting
confidence: 55%
“…Previous studies have shown increased expression of MMPs, COX-2, and iNOS following stimulation of chondrocytes by IL-1β [25]. Thus, the results indicate that nobiletin exerts antiinflammatory effects via attenuation of NF-κB activity.…”
Section: Discussionsupporting
confidence: 55%
“…Two fat-soluble terpenoids of tanshinone IIA from SMRR were identi ed. Tanshinone IIA protects ATDC5 cells from lipopolysaccharide-induced in ammatory injury by downregulating microRNA-203a and inhibiting the JAK/STAT and JNK pathways [32]. Tanshinone IIA can also inhibit the proliferation of chondrocytes, and the degree of inhibition is positively correlated with the concentration of tanshinone IIA.…”
Section: Discussionmentioning
confidence: 98%
“…In addition, experimental studies in rats showed that luteolin could improve the effect of superoxide dismutase (SOD) and catalase induced by selenite, enhance the activity of glutathione peroxidase and glutathione reductase, and then, enhance the activity of the antioxidant enzyme system in organisms [31]. It has also been reported that luteolin can regulate the expression, secretion and activity of MMP-3 by directly acting on articular chondrocytes [32].…”
Section: Discussionmentioning
confidence: 99%
“…To control the progression of the OA, pharmacological and dietary methods have been used [Kaneva et al, ; Xu et al, ]. Previous studies have showed that natural products might be useful for the treatment of OA and rheumatoid arthritis [Kang et al, ; Liu et al, ; Moon et al, ]. CoQ10, an endogenous antioxidant, can suppress the IL‐1β‐induced inflammatory response in some diseases [Fuller et al, ; Schmelzer et al, ].…”
Section: Discussionmentioning
confidence: 99%